Oblikovanje modnih dodatkov in obutve: Zbrano gradivo - Šterman, Sonja (University of Maribor Press, 2020)
Fashion Accesories and Footwear Design: Collected Material. Presented is the role of fashion accessories in the context of fashion, lifestyles and styles, as well as the influence of modern technologies on the development of the field. Developing smart technologies and combining features into fashion accessories gives products new dimensions of functionality that affect quality of life. The field of women’s fashion accessories is divided into jewellery, watches, glasses, headgear, neck accessories, breasts and arms, and also includes haberdashery and handbags, as well as fashion accessories for legs. Men’s accessories include jewellery, watches, glasses, headgear, neck, breast and arm accessories, men’s leather and foot accessories. The historical milestones of the footwear, the classification and parts of footwear and the development guidelines in the field of footwear are presented. The last chapter presents the task of designing footwear for Alpina, d. o. o. Exposed are the starting point of the task, research, concepts and development of models and photographs of made prototypes.